DEVELOPMENT, FEASIBILITY, AND EFFECTIVENESS OF INCLUSIVE STEM MODULE BASED ON SDGS FOR SLOW LEARNERS - Winarni, Kiki Ayu; Akhsan, Hamdi; Kistiono, Kistiono; Anggelina, Putri (EduFisika: Jurnal Pendidikan Fisika, 2025)
Teaching slow-moving learners the abstract science concepts such as Elements, Compounds, and Mixtures can be difficult as they need concrete instructions and less cognitive load. The learning materials available cannot be expected to have the particular accessibility elements that can bridge this cognitive divide. The current study attempts this integration for the first time, combining Universal Design for Learning and a STEM-SDGs approach specifically to support slow learners. The study aimed to create a valid, usable, beneficial-inclusive module for Phase D (Grade VIII) students using the R & D approach (ADDIE model). The study incorporated six expert validators, a practicality trial to slow learners (N=10) and a quasi-experimental field study with 73 learners (Experimental N=34 vs Control N=39). The module had a rating of V-Aiken of 0.87 (Very Valid) and 92.1% was rated as Very Practical. Effectiveness testing showed that the module had a significant positive differentiating factor as the experimental group had evidence of a “High” N-Gain (0.78) as opposed to the Medium (0.40) of the control group. The findings of the study attest that the module based on UDL was effective in bridging difficult concepts and can be an adaptative resource to attain Equity in Science Education.